2014
DOI: 10.1371/journal.pone.0109165
|View full text |Cite
|
Sign up to set email alerts
|

Residency Time as an Indicator of Reproductive Restraint in Male Burying Beetles

Abstract: The cost of reproduction theory posits that there are trade-offs between current and future reproduction because resources that are allocated to current offspring cannot be used for future reproductive opportunities. Two adaptive reproductive strategies have been hypothesized to offset the costs of reproduction and maximize lifetime fitness. The terminal investment hypothesis predicts that as individuals age they will allocate more resources to current reproduction as a response to decreasing residual reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Firstly, males may prolong their involvement in care when caring for highly asynchronous broods in response to the female deserting earlier. In support of this suggestion, we found that males remained with the brood for longer when their partner deserted earlier, and similar results showing that males adjust their contribution to the absence of the female have been found in previous studies on the amount of care (Fetherston et al ., ; Smiseth & Moore, ; Rauter & Moore, ; Smiseth et al ., ; Suzuki & Nagano, ; Smith et al ., ). We found that males responded more strongly to female desertion in highly asynchronous broods, but that the total duration of parental care was similar across all hatching patterns.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Firstly, males may prolong their involvement in care when caring for highly asynchronous broods in response to the female deserting earlier. In support of this suggestion, we found that males remained with the brood for longer when their partner deserted earlier, and similar results showing that males adjust their contribution to the absence of the female have been found in previous studies on the amount of care (Fetherston et al ., ; Smiseth & Moore, ; Rauter & Moore, ; Smiseth et al ., ; Suzuki & Nagano, ; Smith et al ., ). We found that males responded more strongly to female desertion in highly asynchronous broods, but that the total duration of parental care was similar across all hatching patterns.…”
Section: Discussionmentioning
confidence: 97%
“…We used the amount of time that each parent spent with the brood from the arrival of the first larvae as a proxy for the amount of care they provided (Boncoraglio & Kilner, 2012;Smith et al, 2014). We checked each box twice a day (at 09:00 and 17:15 h) to determine whether the parent was present or absent from the brood chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The burying beetle, Nicrophorus orbicollis , is an ideal system for studying evolution of parental care because we can directly address each of the difficulties outlined above. First, although they are typically biparental, each parent is capable of rearing offspring alone [ 5 8 ]. The facultative nature of biparental care in this species of burying beetle provides opportunity to experimentally assess fitness of parental care strategies within the normal range of behaviors for the species.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, both parents bury and preserve the carcass and feed and protect larvae until they disperse, and both parents regulate brood size through filial cannibalism [ 9 ]. Although males generally abandon the brood before the female, they usually remain with the female and the larvae until the larvae reach the third instar stage of development [ 6 , 8 , 10 11 ]. Second, the costs and benefits of biparental and uniparental reproductive strategies can be quantified relative to a known resource amount.…”
Section: Introductionmentioning
confidence: 99%